Clinical chorioamnionitis criteria are not sufficient for predicting intra-amniotic infection. (2nd January 2022) - Maki, Yohei; Furukawa, Seishi; Nakayama, Tetsuo; Oohashi, Masanao; Shiiba, Nozomi; Furuta, Ken; Tokunaga, Shuuichi; Sameshima, Hiroshi
Abstract: Aim: To evaluate the diagnostic performance of three conventional clinical chorioamnionitis criteria; including Gibbs, Lencki, and suspected triple I; for the prediction of intra-amniotic infection. Methods: A retrospective cohort study was conducted using data from three perinatal centers from 2014 to 2018. Patients with preterm labor or premature prelabor rupture of membranes between 22 and 33 weeks of gestation and those who underwent transabdominal amniocentesis to detect intra-amniotic infection were selected. Intra-amniotic infection was defined as a positive amniotic fluid culture for microorganisms, including genital mycoplasmas, plus low glucose level or leukocytosis in amniotic fluid. Sensitivity, specificity, and positive and negative likelihood ratios were calculated to determine the diagnostic performance of each criterion in predicting intra-amniotic infection. Results: Of 99 pregnant women who met the study inclusion criteria, 13 (13.1%) had intra-amniotic infection confirmed by amniocentesis and 86 (86.9%) had no intra-amniotic infection. Maternal characteristics were not significantly different between groups, except for the higher incidence of preterm, prelabor rupture of membranes in pregnant women with intra-amniotic infection (53.8 versus 14%, p < .01). The incidences of clinical chorioamnionitis in the non-IAI and IAI groups were 1 of 86 (1.2%), 1 of 86 (1.2%), 0 of 86 (0%) and 2 of 13 (15.4%), 2 of 13 (15.4%), 2 of 13 (15.4%) according to Gibbs, Lenki, and suspected triple I criteria, respectively. The specificity of the three criteria ranged from 98.8 to 100%; however, the sensitivity was low (15.4%). The positive likelihood ratio was significant for three criteria from 13.2 (95% confidence interval [CI], 1.29–135) to infinite. However, the negative likelihood ratio was not low enough and not significant for the three criteria (0.85 [95% CI, 0.67–1.07] to 0.86 [95% CI, 0.68–1.08]). Conclusion: The conventional clinical chorioamnionitis criteria are not sensitive for the prediction of intra-amniotic infection in pregnant women with preterm labor and/or preterm prelabor rupture of membranes.